UMP invited to attend 2019 Chinese New Year Reception Celebration at the Embassy of People’s Republic of China - Yong, Ying Mei (2019)
27 January 2019- Universiti Malaysia Pahang (UMP) was invited to attend “2019 Chinese New Year Reception Celebration” which was organized by Embassy of the People’s Republic of China in Malaysia at Shangri-La Hotel, Kuala Lumpur. UMP invited guests were Professor Dato’ Sri Ts. Dr. Daing Nasir Ibrahim (Vice Chancellor UMP) Datin Sri Fazia Binti Ali (Head of Deputy Registrar, Research and Innovation Department) and Ms. Yong Ying Mei (Director of Confucius Institute).